Reducing Overflow by Using Storage Analysis Chart at PT. Mitratama Autopart Company - Aliyuslita Aliyuslita; Anastasia L Maukar (JIE Scientific Journal on Research and Application of Industrial System, 2016)
Factory is a very common location in industrial field, where the most problem occurred. By observing the local part that is used for production welding plant 1 in PT. Mitratama, some part are often returned. The problem was happening because the capacity flow rack cannot hold all of the box supplied. Resulting in re-arrangement of the quantity in box, so the number of box used is decreasing for the next supply. One of the solutions is increasing the box capacity and the other one is by standardize the flow rack measurement. Therefore, Storage Analysis Chart is used to identify the capacity of regular production safety stock, type of rack, and the area requirement. Internal lead time and stock capacity in the flow rack of production line also become consideration. Storage Analysis Chart can provide the improvement by optimizing the measurement and its space. Then standardization is implemented so the rack capacity will be improved. So, all the box from the progress lane can be supplied to production. The results of the standardization that has been implemented are the overflow will be reduced by 1.54% and the area of direct supply also reduced by 50%.